Modelling and fabrication of flexible strain sensor using the 3D printing technology [2] - Gunes, Seyhmus; Ülkir, Osman; Kuncan, Melih (SAGE Publications Ltd, 2025)
The use of additive manufacturing (AM) or 3D printing in sensor technology is increasing daily because it can fabricate complex structures quickly and accurately. This study presents the modeling, fabrication, and characterization processes for the development of a resistance type flexible strain sensor. The finite element model of the sensor was developed using COMSOL software and was verified experimentally. The experimental results agreed well with the simulation results. The fabrication process was performed using the molding technique. The flexible substrate of the strain sensor was fabricated by fused deposition modeling (FDM), an AM method, with dimensions of 20 mm × 60 mm and a thickness of 2 mm. In this process, a flexible and durable elastomer material called thermoplastic polyurethane (TPU) was used. The liquid conductive silver was then injected into the mold channels. The characterization process was performed by establishing experimental and numerical setups. Studies were conducted to maximize sensitivity by changing the geometric properties of the sensor. At the 30% strain level, sensitivity increased by 9% when the sensor thickness decreased from 2 to 1.2 mm. As a result of the gradually applied force, the strain sensor showed a maximum displacement of 34.95 mm. Tensile tests were also conducted to examine the effects of stress accumulation on the flexible base. The results of this study show that the strain sensor exhibits high linearity-sensitivity and low hysteresis performance. © 2025 Elsevier B.V., All rights reserved.
Keywords: Additive Manufacturing; Finite Element Model; Flexible Strain Sensor; Fused Deposition Modeling; Thermoplastic Polyurethane; Reinforced Plastics; Thermoplastics; 3-d Printing; 3d-printing; Complexes Structure; Deposition Modeling; Finite Element Modelling (fem); Flexible Strain Sensor; Printing Technologies; Sensor Technologies; Strain Sensors; Thermoplastic Polyurethanes; Tensile Testing